Comparing the usability and reliability of a generic and a domain-specific medical error taxonomy - Taib, Ibrahim Adham; McIntosh, Andrew Stuart; Caponecchia, Carlo; Baysari, Melissa T. (Elsevier, 2012)
Medical error taxonomies are used to report and analyse patient safety incidents. Medical error taxonomies can be generic or domain-specific. In comparing generic and domain-specific medical error taxonomies, the literature compares the information both type of taxonomies classify. There is little evidence the taxonomies have been compared in terms of usability and reliability. Twenty nurses and 21 pharmacists participated in a study comparing the usability and reliability of a generic medical error taxonomy and a medication error taxonomy. The medical error taxonomies utilized were the Patient Safety Event Taxonomy and the NCC MERP Taxonomy of Medication Error. The study found no significant difference in the usability ratings of both taxonomies. The taxonomies required different amount of time to classify patient safety incidents and had significantly different reliability levels. The reliability of the NCC MERP Taxonomy of Medication Error was significantly different when used by nurses and pharmacists. The taxonomy was also preferred by the majority of participants. Some recommendations are made about the design of future medical error taxonomies.